A Review on Antimony-based Perovskite Solar Cells - Ankit Stephen Thomas (Equilibrium Journal of Chemical Engineering, 2022)
ABSTRACT. Over the past decade, lead halide perovskite light absorbers have been the conventionally used perovskite light absorbers. However, there is an urgent call for alternative perovskite materials with toxicity levels and poor stability to UV radiations. Antimony-based perovskites have proven to be a material with unique optoelectronic properties, conventional fabrication processes, low-toxicity levels and high stability values. In this review, we look into the structure of antimony perovskites, the various research achievements over recent years, and the challenges and opportunities ahead for this budding technology. The review also highlights the various computational, theoretical and experimental studies done by researchers to highlight the peculiar Lead-free perovskite materials and their distinctive features. Although the efficiency levels of these devices are not very high, the improvements they have made with remarkable stability characteristics make them a viable candidate for commercial perovskite photovoltaics.Keywords: Perovskite Solar Cells, Photovoltaic Technology, Leadfree Perovskites, Solar Cell Materials, Antimony-based Perovskites